Factors of radicalisation towards terrorism based on the case formulation framework - Mohamed Noor, Nurnadiah (2017)
Radicalisation, being closely linked to terrorism, brings about negative impacts in the society, hence warranting a more thorough understanding of the problem. Previous literature in the field have provided single explanations, ordered progression of events as well as profiles of radicalised individuals to explain radicalisation. This paper thus seeks to better understand the underlying dynamics of radicalisation using the case formulation framework – specifically the influences of the predisposing, precipitating, perpetuating, and protective factors on the presenting issues – as it may offer a more dynamic and comprehensive understanding of the various influences towards the radicalisation process. Leading factors of radicalisation such as demographics, sense of identity and belonging, socialisation, grievance, motivation, ideology, and resilience are reviewed, and their categorisation into each element of the framework is proposed. Avenues for future research in understanding the radicalisation process are also suggested, focusing on more evidence-based and controlled studies as well as analysing possible interactions between different factors.